Single and Double Brillouin Frequency Spacing Multi-Wavelength Brillouin Erbium Fiber Laser With Micro-Air Gap Cavity - Tiu, Zian Cheak; Aidit, S.N.; Hassan, N.A.; Ismail, Mohammad Faizal; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2016)
Single and double Brillouin frequency spacing multi-wavelength Brillouin Erbium-doped fiber laser based on micro-air gap cavity is proposed and demonstrated. A 6.90-km dispersion shifted fiber is used as Brillouin gain medium to induce stimulated Brillouin scattering in the ring cavity. The micro-air gap cavity is constructed by aligning two polished fiber facets coaxially, and induces strong Fresnel reflection to switch the Brillouin frequency spacing from a double spacing to single spacing regime. Under the Brillouin pump power of 13 dBm and the laser diode pump power of 300 mW, five Stokes with a wavelength spacing of 0.160 nm and six Stokes with a wavelength spacing of 0.084 nm are generated. The fluctuation of the Stokes for both single and double Brillouin spacing regimes in the proposed setup are less than 3 dB throughout a 1-h time span. The variation of the cavity efficiency between the single and double spacing regimes is less than 1.2 dB.